Structural and morphological studies of polypropylene/kaolin nanocomposite - Yahaya, Shehu; Jikan, Suzi Salwah; Badarulzaman, Nur Azam; Adamu, Ajiya Dahiru (American Scientific Publishers, 2018)
Nanocomposite of polypropylene (PP) was made by melt intercalation technique with nanokaolin. Kaolin particles were modified with urea by intercalation to produce nanokaolin. Structural and morphological analyses of polypropylene/kaolin nanocomposite was investigated by Fourier Transform Infrared (FT-IR) spectroscopy and Field Scanning Electron Microscopy (FESEM). The interaction of FT-IR confirms hydrogen bonds formed between urea molecules and the inner surface of kaolin layers. It also gives evidence that kaolin was dramatically delaminated into nano scale by intercalation activity. Whereas, FESEM shows kaolin particles were homogeneously dispersed into the PP matrix.